Captain Underpants and the wrath of the wicked Wedgie Woman - Pilkey, Dav, 1966- (Scholastic, Inc., 2018)
When Harold and George turn fourth-grade teacher Ms. Ribble into the evil Wedgie Woman, she gives the wedgie of doom to unsuspecting people who stand in her way--including principal-turned-superhero Captain Underpants.